How do financial development and environmental policy stringency affect renewable energy innovation? The Porter Hypothesis and beyond - Songran Li; Qinglong Shao (Journal of Innovation & Knowledge (JIK), 2023)
Multiple studies have examined the effects of financial development on renewable energy consumption, but little is known about its impact on renewable energy innovation. The validity of the Porter Hypothesis (PH) in renewable energy industries-that is, whether stricter environmental policies promote innovation-remains unclear. This study explores the effects of financial market development and environmental policy stringency on renewable energy innovation, as well as whether renewable innovation differs with levels of stringency of environmental policy and levels of development of the financial market. We apply a nonlinear panel threshold model to the 37 member countries of the organization for Economic Co-operation and Development (OECD) from 1990 to 2019. The results show that as financial development increases, its impact gradually declines, and that as environmental policy becomes more stringent, its impact rapidly increases. This finding implies that financial development is associated with greater increases in renewable innovation in countries with a medium level of financial development, and that stricter environmental policies can be used by OECD countries to increase innovation. This study therefore confirms the validity of the PH as well as the financial development effect on renewable innovation in OECD countries. It also finds that international oil prices and the level of research and development expenditure have significantly positive effects on renewable innovation. Policy suggestions for developing financial markets and increasing policy stringency are proposed.
Keywords: G28; O3; Q28; 650; Environmental policy stringency; Financial market development level; Panel threshold model; Porter Hypothesis (PH); Renewable energy innovation